Nutritional and sensory characteristics determination of fortified cookies with cushuro (Nostoc sphaericum Vaucher) and tarwi (Lupinus mutabilis Sweet) - Valencia-Fajardo, Rafael (2024)
The nutritional and sensory characteristics of food products are important for their acceptance by the consumer. The objective of this research was to evaluate cookies fortified with cushuro and tarwi, two ingredients that stand out for their nutritional properties and potential health benefits. Cushuro, an algae that grows in high-altitude lakes in the Andes, is important for being an excellent source of proteins, vitamins, and minerals such as iron and calcium. On the other hand, tarwi, an Andean legume, is rich in proteins, fiber, and fatty acids, making it a highly nutritious food. The idea of fortifying cookies with cushuro and tarwi arises from the seek for alternatives to enhance the nutritional content of processed foods. Given that cookies are widely consumed, especially by children and adults, incorporating nutrient-rich ingredients like cushuro and tarwi can significantly contribute to a more balanced and healthy diet. The inclusion of these ingredients in cookies could not only improve their nutritional profile but also offer an appealing option for those seeking foods with added value. To assess the impact of these ingredients on cookies, two types were prepared: ones with cushuro and tarwi and ones without. This approach allows us to compare how the addition of cushuro and tarwi affects both the sensory and nutritional characteristics of the cookies, thus providing a comprehensive view of their potential as a food product.